Effectiveness of Tinospora cordifolia in comparison to tramadol for analgesic activity in albino rats - Syed Gulam Ahmed; Suguna Sajja; Bhuvaneswari Edavaluru; Shravya Edavaluru; Praneeth Reddy Onteddu (Asian Journal of Medical Sciences, 2023)
Background: Pain and pyrexia are the warning signals, primarily protective in nature, that cause discomfort and suffering and may even be unbearable and incapacitating. The modern drugs (such as opioids, NSAIDs, and corticosteroids) currently used for the management of pain, fever, and inflammatory conditions, present with many known adverse effects. Tinospora cordifolia known as Giloe or guduchi, widely used in folk medicine due to its property to cure several diseases. Aims and Objectives: The present study was undertaken to explore the analgesic activity of water-soluble extract of T. cordifolia in albino rats in experimentally induced pain. Materials and Methods: The present study was done in the Department of Pharmacology, Gandhi Medical College, Secunderabad. Albino rats were used to study the analgesic activity of T. cordifolia aqueous extract at the dose of 300 mg/kg and 1 g/kg and tramadol 50 mg/kg per orally. Eddy’s hot plate was used for the antinociceptive study. Results: In Eddy’s hot plate, an increase in reaction time was observed with peak effect at 90 min. Results were close to the standard drug tramadol. Conclusion: Aqueous extract of T. cordifolia was effective in model of pain suggesting its possible action by central and peripheral mechanisms, and in higher doses, it was found to be effective like that of tramadol.